Takror Sebagai Tradisi Pengembangan Pembelajaran Santri Di Pondok Pesantren - Mawi Khusni Albar (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2018)
Abstract: Pesantren since their appearance have given many colors in this country. This includes the many traditions that until now are still feasible to be developed in the current era. Takror is a method of learning in Islamic boarding schools, especially in Islamic boarding schools. Takror is a solution that is expected to involve clerics with their students, so that they can interact in learning, also have a strong impact on understanding the material that has been taught by the teacher, and foster a high courage and confidence to reflect their knowledge in front of others both individually and collective. Keywords: Pesantren, Takror, Rigiditas Kurikulum